2014
DOI: 10.1007/s00059-014-4154-6
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c levels as predictors of ablation outcome in type 2 diabetes mellitus and paroxysmal atrial fibrillation

Abstract: High levels of HbA1c were associated with an increased risk of recurrence of atrial tachyarrhythmia in patients with T2DM and PAF undergoing catheter ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 26 publications
1
23
0
1
Order By: Relevance
“…Of the 14 selected studies, 3 studies [4,9,13] reported that higher HbA1c levels increase the risk of AF, 3 studies [7,8,14] demonstrated that higher HbA1c levels are a protective factor for AF, and the remaining eight studies [5,6,11,1519] showed no significant association between HbA1c levels and AF.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 14 selected studies, 3 studies [4,9,13] reported that higher HbA1c levels increase the risk of AF, 3 studies [7,8,14] demonstrated that higher HbA1c levels are a protective factor for AF, and the remaining eight studies [5,6,11,1519] showed no significant association between HbA1c levels and AF.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it is known that the LA and LV in patients with these two metabolic disorders are typically affected by extensive fibrosis; this fibrosis also represents a cardinal feature of both HFpEF and longstanding AF . Unfortunately, patients with AF who have myocardial fibrosis are unlikely to maintain sinus rhythm following an ablation procedure; this is likely to explain the high rate of AF recurrence following catheter ablation in patients with obesity or type 2 diabetes …”
Section: Therapeutic Challenges In Patients With a Metabolic Disordermentioning
confidence: 99%
“…Among patients with AF who undergo ablation, those who have increased LA dimensions, pressures or fibrosis, or LV fibrosis or abnormal diastolic filling parameters are at increased risk for AF recurrence and often require repeated ablation procedures; in patients without a prior myocardial infarction (i.e. HFpEF), the finding of ventricular fibrosis doubles the procedural failure rate .…”
Section: Therapeutic Challenges In Patients With a Metabolic Disordermentioning
confidence: 99%
“…Similarly, biomarkers of an underlying HFpEF (ie, abnormalities of LV diastolic filling or left atrial geometry) identify patients who are unlikely to achieve and sustain sinus rhythm, whether the AF is treated electrically or pharmacologically . Additionally, both obesity and diabetes are accompanied by a high rate of AF recurrence following catheter ablation . Procedural success following ablation is diminished by LA fibrosis, which is a common finding in both metabolic disorders, especially if the AF is long‐standing or is accompanied by latent HFpEF …”
Section: Heightened Risks Of Rate‐control Strategies For Af In Obesitmentioning
confidence: 99%
“…[54][55][56] Additionally, both obesity and diabetes are accompanied by a high rate of AF recurrence following catheter ablation. 57,58 Procedural success following ablation is diminished by LA fibrosis, which is a common finding in both metabolic disorders, especially if the AF is long-standing or is accompanied by latent HFpEF. 59,60…”
Section: Heightened Risks Of Rate-control Strategies For Af In Obesmentioning
confidence: 99%